Code switching found in domani siblings podcast Prilly Latuconsina speak up youtube channel - Dharmayanti, Ni Nyoman Trisna; Putri, I Gusti Ayu Vina Widiadnya (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
This study investigated the types also functions of code-switching in Prilly Latuconsina's speak up on the Domani Siblings Podcast on YouTube. The analysis was as per Poplack's (1980) theory of code-switching types also Appel & Muysken's (1987) theory of code-switching functions. A descriptive-qualitative approach was employed. Data were collected through observation, video analysis, also note-taking. The result of this study finding were 82 datas. The findings revealed all types of code-switching: inter-sentential switching 3, tag switching 18, also intra-sentential switching 61, along with five functions: metalinguistic function 16, directive function 14, poetic function 3, expressive function 4, also referential function 45.